Cerebral Palsy - Madjidova, G. T.; Nuralieva, G. B.; Buribaeva, A. X. (American Journal of Bioscience and Clinical Integrity, 2024)
Cerebral palsy (CP) is a non-progressive neurological disorder resulting from damage to the central nervous system during the prenatal, perinatal, or neonatal periods. It is a leading cause of childhood disability, with a prevalence of 2-2.5 cases per 1000 children. This condition often coexists with various intellectual, speech, and paroxysmal disorders. Classification of CP is complex due to its heterogeneous nature and is based on predominant movement disorders, which can be spastic, dyskinetic, ataxic, or mixed. Approximately 50% of cases occur in children born prematurely, with risks increasing as gestational age and birth weight decrease. Risk factors for CP include maternal infections, coagulopathies, and complications during birth. Symptoms range from motor impairments to cognitive and behavioral disorders, with the diagnosis typically confirmed by 12-18 months of age. While CP cannot be cured, rehabilitation efforts can significantly improve functional outcomes. These efforts may include physiotherapy, occupational therapy, speech therapy, and pharmacological treatments aimed at symptom management. Surgical interventions may be considered in cases of severe spasticity or contractures.